A protocol for a systematic review of process evaluations of interventions investigating sedentary behaviour in adults. Issue 9 (18th September 2019) - Corepal, Rekesh; Hall, Jessica Faye; English, Coralie; Farrin, Amanda; Fitzsimons, Claire F; Forster, Anne; Lawton, Rebecca; Mead, Gillian; Clarke, David
Abstract : Introduction: Sedentary behaviour is defined as any waking behaviour characterised by low energy expenditure ≤1.5 metabolic equivalents while in a sitting, lying or reclining posture. The expanding evidence base suggests that sedentary behaviour may have a detrimental effect on health, well-being and is associated with an increased risk of all-cause mortality. We aim to review process evaluations of randomised controlled trials (RCTs) which included a measure of sedentary behaviour in adults in order to develop an understanding of intervention content, mechanisms of impact, implementation and delivery approaches and contexts, in which interventions were reported to be effective or effective. A secondary aim is to summarise participants, family and staff experiences of such interventions. Methods and analysis: Ten electronic databases and reference lists from previous similar reviews will be searched. Eligible studies will be process evaluations of RCTs that measure sedentary behaviour as a primary or secondary outcome in adults. As this review will contribute to a programme to develop a community-based intervention to reduce sedentary behaviour in stroke survivors, interventions delivered in schools, colleges, universities or workplaces will be excluded. Two reviewers will perform study selection, data extraction and quality assessment. Disagreements between reviewers will be resolved by a third reviewer. Process evaluation data to be extracted include the aims and methods used in the process evaluation; implementation data; mechanisms of impact; contextual factors; participant, family and staff experiences of the interventions. A narrative approach will be used to synthesise and report qualitative and quantitative data. Reporting of the review will be informed by Preferred Reporting Items for Systematic Review and Meta-Analysis guidance. Ethics and dissemination: Ethical approval is not required as it is a protocol for a systematic review. Findings will be disseminated through peer-reviewed publications and conference presentations. PROSPERO registration number: CRD42018087403.